MODELING OF THE BEAM SWEEPING PROCESS DURING INITIAL ACCESS IN 5G NR NETWORKS - BOIKO, JULIY; PYATIN, ILYA; GAVRONSKIY, VITALIY; KOROTUN, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper discusses the procedures for controlling the 5G beam. A packet of the NR synchronization signal is generated and a beam of each SSB in the packet is formed, which allows scanning in the azimuth and elevation directions. The formed beam is transmitted via a spatial scattering channel. The received signal is processed using several receiver beams, the power of the received reference signal (RSRP) is measured for each pair of transmit-receive beams, and the best pair of beams with the maximum RSRP is determined. The spectrogram of the synchronization signal packet, the directivity diagrams of the transmitter and receiver antennas are studied. The indicators that allow evaluating the synchronization signal packet are considered: RSRP, RSSI, RSRQ levels at different frequency bandwidths, a map of RSRP values, which allows you to visually see which pair of beams gives the highest power of the received signal. The reference grid of the primary synchronization signal is considered. The beam sweep on the transmitter side is studied. The control vector for the transmitter antenna array has been calculated, the angle of the scatterer relative to the antenna array has been determined. The signal propagation losses and the mean square noise value at the receiver have been studied depending on the distance between the transmitter and the receiver. The beam width in azimuth has been studied depending on the number of antennas in the antenna array. The beam width in azimuth and elevation has been studied depending on the control direction. The investigated Beam Sweeping and Beam Determination procedures indicate that transmitting eight SSB blocks every 20 ms (one full sweep on the gNB side) requires 8×20 = 160 ms for a full duplex sweep (8 Tx × 8 Rx) if the UE changes direction for each SSB packet. From the results of the study of signal loss versus distance, it can be concluded that at a distance between the transmitter and receiver of 700 m, when changing the frequency from 0.9 to 45 GHz, the path loss increases by 35 dB, while the root mean square (RMS) noise value on the receiving antenna decreases by 55 dB. When studying the beam width in azimuth from the number of antennas in the antenna array at different distances between antenna elements, it can be concluded that the beam width decreases with an increase in the number of antenna elements in the array and an increase in the distance between antenna elements. When studying the beam width from the control direction in a three-dimensional plane, it can be concluded that the central angles of the beam in the direction of wave propagation have a smaller width. At the edges of the control range (±60° in azimuth), the beam will be wider due to larger side lobes.
Keywords: beam steering; millimeter waves; radiation pattern; beam scanning; phased array antenna; 5G